Enhancing Economic Development through Economic Empowerment: Challenges for Women (Journal of Governance and Development (JGD), 2015)
Status of women around the world varies among parts of the world. Some developing countries like Africa, the status of women is low compared to the developed countries. There is an urgent need to give attention to the needs and problems of women to enable them to enjoy and exercise their rights and opportunities; thus, women can be part of a group contributing to national development. Generally, women and economy often are separated as two different identities in enhancing the sustainable economy. The facts that the number of women working in the industries is less than the number of men are no longer false. Therefore, the paper aims to discuss women empowerment specifically in regard to economic empowerment. Three elements, namely microfinance, education and legal aid that contribute towards economic empowerment for women also will be argued in the paper. The challenges women faced towards achieving economic empowerment also will be discussed.